Method for preparing high-closed-pore perlite by chemical modification gradient temperature rising

Through the chemical modification gradient temperature rising method, the pore structure of perlite is optimized, the closed porosity and mechanical stability are improved, which solves the problem of low closed porosity of traditional perlite and broadens its application in high-end insulation and moisture-proof fields.

CN120136567BActive Publication Date: 2025-10-17LANGFANG INCOM SCI&TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510625057.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-05-15
Publication Date
2025-10-17
Estimated Expiration
2045-05-15

AI Technical Summary

Technical Problem

Perlite prepared by traditional methods has a low closed porosity, resulting in high water absorption and large thermal conductivity, which affects its application performance in high-end insulation, moisture-proofing and other fields.

Method used

The chemical modification gradient temperature rise method is adopted, including pretreatment, chemical modification treatment and gradient temperature rise calcination, combined with the use of silicon-based modifiers and surfactants, through gradient temperature rise and inert gas protection, to achieve systematic optimization of the perlite pore structure.

Benefits of technology

It significantly increases the closed porosity of perlite, reduces thermal conductivity, and improves mechanical stability and environmental adaptability, making it suitable for high-end fields such as vacuum insulation panels and LNG storage tank cold insulation layers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120136567B_ABST
    Figure CN120136567B_ABST
Patent Text Reader

Abstract

The application provides a method for preparing high-closed-pore perlite by chemical modification and gradient temperature increase, and belongs to the technical field of high-closed-pore perlite preparation, and comprises the following steps: (1) pretreatment: crushing and screening the perlite raw ore to a particle size of 30-50 μm, washing with acid and deionized water to neutral, and drying after controlling the moisture content to be 8-12%; (2) chemical modification treatment: immersing the pretreated perlite in a composite solution containing a silicon-based modifier and a surfactant, the immersion liquid-solid ratio being (5:1)-(10:1), the immersion temperature being 40-60 DEG C, and the immersion time being 1-2 h, and then drying; (3) gradient temperature increase roasting; (4) post-treatment. The application realizes systematic optimization of the pore structure of the perlite, the unique gradient temperature increase strategy accurately matches the thermal expansion characteristics of the perlite at different temperature stages, effectively reduces the risk of structure cracking, and guarantees the uniformity and stability of the closed pores.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of high-closed-pore perlite preparation, in particular to a method for preparing high-closed-pore perlite by chemical modification and gradient temperature rise. BACKGROUND

[0002] Perlite is a common porous inorganic non-metallic material, which has a wide range of applications in building insulation, agricultural horticulture, industrial filtration and many other fields due to its good thermal insulation, light weight and other characteristics. However, the traditional method of preparing perlite has the problem of low closed-pore rate, and a large number of open-pore structures make the water absorption rate of perlite high and the thermal conductivity large, which seriously affects its application performance in high-end thermal insulation, moisture-proof and other fields.

[0003] The existing technology for improving the closed-pore rate of perlite mostly uses single physical treatment or simple chemical modification, which cannot systematically optimize the pore structure of perlite. For example, simple high-temperature calcination cannot control the formation of pore structure of perlite during the expansion process, and is prone to structure cracking, uneven closed-pores and other situations; and the use of single chemical modifier cannot fully exert the modification effect and is difficult to realize precise control of the pore structure.

[0004] Therefore, a preparation method capable of systematically optimizing the pore structure of perlite and significantly improving the closed-pore rate is proposed. SUMMARY

[0005] The present application provides a method for preparing high-closed-pore perlite by chemical modification and gradient temperature rise, which aims to solve the problems in the background art.

[0006] The specific technical solution is as follows:

[0007] A method for preparing high-closed-pore perlite by chemical modification and gradient temperature rise, comprising the following steps:

[0008] (1) Pretreatment: crushing and sieving the perlite ore to a particle size of 30-50 μm, washing with acid and deionized water to neutral, controlling the moisture content to be 8%-12%, and then drying;

[0009] (2) Chemical modification treatment: immersing the pretreated perlite in a composite solution containing a silicon-based modifier and a surfactant, with a liquid-to-solid ratio of (5:1)-(10:1), an immersion temperature of 40-60℃, and an immersion time of 1-2 h, and then drying;

[0010] (3) Gradient temperature rise calcination: placing the modified perlite in a high-temperature furnace and performing three-stage gradient temperature rise:

[0011] First stage: rising to 200-500℃ at a rate of 5-10℃ / min, and keeping the temperature for 0.5-1 h;

[0012] The second stage: heating to 600-900℃ at 3-20℃ / min, keeping warm for 1-20min;

[0013] The third stage: heating to 1000-1200℃ at 1-12℃ / min, keeping warm for 2-10min and then cooling;

[0014] (4) Post-processing: Inert gas protection is introduced during the cooling process, and high closed-porosity perlite with a closed-porosity of ≥85% is obtained after screening.

[0015] The above-mentioned method for preparing high closed-porosity perlite by chemical modification and gradient heating, wherein the silicon-based modifier is a mixture of a silane coupling agent and a phosphate, the silane coupling agent is selected from KH550 and KH560, the mass ratio is (1:0.5)-(1:2), and the phosphate concentration is 0.5-2 mol / L; or the silicon-based modifier is a sodium silicate solution with a mass fraction of 8% to 12%, and the surfactant is sodium dodecylbenzene sulfonate with a mass fraction of 0.5% to 2%.

[0016] In the above-mentioned method for preparing high closed-porosity perlite by chemical modification and gradient heating, when a silane coupling agent is used, the gradient heating parameters are:

[0017] The first stage: heating to 400-500℃ at 5-10℃ / min, keeping warm for 30-60min;

[0018] The second stage: heating to 800-900℃ at 15-20℃ / min, keeping warm for 10-20min;

[0019] The third stage: heat up to 1050-1150℃ at 8-12℃ / min and keep warm for 5-10 minutes.

[0020] In the above-mentioned method for preparing high closed-porosity perlite by chemical modification and gradient heating, when sodium silicate solution is used, the gradient heating parameters are:

[0021] Stage 1: Heat up to 230-270°C at 6-8°C / min, and keep warm for 0.5-1h;

[0022] The second stage: heating to 620-680℃ at 3-4℃ / min, keeping warm for 1-2h;

[0023] The third stage: heat up to 1050-1150℃ at 1-1.5℃ / min and keep warm for 2-3h.

[0024] The above-mentioned method for preparing high closed-porosity perlite by chemical modification and gradient heating, wherein, in step (1), microwave pretreatment is performed before drying, with a microwave power of 300-800W and a treatment time of 3-5 minutes.

[0025] In the above-mentioned method for preparing high closed-porosity perlite by chemical modification and gradient heating, after the third stage of step (3) is completed, nitrogen protection cooling is performed to below 600°C, with a gas flow rate of 0.5-1.5 L / min.

[0026] In the above-mentioned method for preparing high closed-porosity perlite by chemical modification and gradient heating, the screening in step (4) is performed using a double-layer vibrating screen with an upper layer of 100 mesh and a lower layer of 200 mesh, to obtain perlite with a pore gradient distribution: the porosity of the surface layer is ≤5%, the porosity of the middle layer is 40% to 60%, and the core layer is 70% to 85%.

[0027] In the above-mentioned method for preparing high closed-porosity perlite by chemical modification and gradient heating, after the second stage of step (3) is completed, the furnace door is opened to release the pressure to 80% to 90% of the normal pressure for a duration of 30-60 seconds.

[0028] The high closed-porosity perlite prepared by the above-mentioned chemically modified gradient temperature-increasing method has a closed-porosity of ≥95% and a thermal conductivity of ≤0.035 W / (m·K), and is suitable for vacuum insulation panels or cold insulation layers of LNG storage tanks.

[0029] The closed porosity detection method of the high closed porosity perlite prepared by the above-mentioned method of preparing high closed porosity perlite by chemical modification and gradient heating is as follows:

[0030] The mercury intrusion method was combined with micro-CT three-dimensional reconstruction, according to the formula:

[0031]

[0032] The closed porosity was calculated, where the open pore volume was determined by nitrogen adsorption and the total pore volume was determined by mercury intrusion.

[0033] The present invention has the following beneficial effects:

[0034] The present invention achieves systematic optimization of the perlite pore structure by integrating a complete process chain of pretreatment, chemical modification, gradient heating and post-treatment. The unique gradient heating strategy accurately matches the thermal expansion characteristics of perlite at different temperature stages, effectively reducing the risk of structural cracking and ensuring the uniformity and stability of closed cells.

[0035] Two chemical modification systems, namely the silane coupling agent and phosphate mixture system and the sodium silicate and surfactant system, can be flexibly selected according to different application scenarios. The former enhances surface activity through chemical bonding, while the latter optimizes pore distribution through physical adsorption and ion exchange, greatly expanding the applicability of the process.

[0036] The microwave pretreatment improves the modification liquid permeation efficiency and surface activity, the inert gas protection cooling inhibits oxidation, the double-layer screening realizes the pore gradient distribution, and the pressure regulation optimizes the closed pore structure. The synergistic effect of various technologies significantly improves the closed pore rate of perlite, so that the perlite has excellent thermal insulation performance, mechanical stability and environmental adaptability, and can be widely applied to high-end fields such as vacuum insulation panels and LNG storage tank cold insulation layers, and effectively fills the application blank of traditional perlite in these fields. BRIEF DESCRIPTION OF DRAWINGS

[0037] Figure 1 The flow chart of the method for preparing high-closed-pore-rate perlite by chemical modification gradient warming provided by the embodiment of the present application is shown in the figure.

[0038] Figure 2 The curve graph of the closed pore rate of the high-closed-pore-rate perlite prepared by the present application changing with temperature stages is shown in the figure.

[0039] Figure 3 The curve graph of the compressive strength of the high-closed-pore-rate perlite prepared by the present application changing with porosity is shown in the figure.

[0040] Figure 4 The curve graph of the mass loss rate of the high-closed-pore-rate perlite prepared by the present application changing with temperature is shown in the figure.

[0041] Figure 5 The temperature-time change curve graph of the high-closed-pore-rate perlite prepared by the embodiments 1-3 of the present application is shown in the figure.

[0042] Figure 6 The closed pore rate and thermal conductivity column graph of the high-closed-pore-rate perlite prepared by the embodiments 1-3 of the present application is shown in the figure. DETAILED DESCRIPTION

[0043] The technical solutions of the present application will be further described below by combining the drawings and through specific embodiments.

[0044] Among them, the drawings are only used for example explanation, and the representation is only a schematic diagram, not a real object diagram, and cannot be understood as a limitation of the present patent; in order to better illustrate the embodiments of the present application, some components of the drawings will be omitted, enlarged or reduced, and do not represent the size of the actual product; for those skilled in the art, it is understandable that some known structures and their descriptions in the drawings can be omitted.

[0045] The same or similar reference numerals in the drawings of the embodiments of the present application correspond to the same or similar components; in the description of the present application, it should be understood that if the terms "upper", "lower", "left", "right", "inner", "outer" and the like indicating the orientation or positional relationship are based on the orientation or positional relationship shown in the drawings, they are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the devices or elements referred to must have a particular orientation, be constructed and operated in a particular orientation, therefore the terms describing the positional relationship in the drawings are only used for exemplary illustration, and cannot be understood as a limitation on the present patent, for those skilled in the art, the specific meanings of the above terms can be understood according to the specific circumstances.

[0046] In the description of the present application, unless otherwise explicitly specified and limited, if the term "connection" and the like indicating the connection relationship between components appears, the term should be broadly understood, for example, it can be fixedly connected, or it can be detachably connected, or it can be integrated; it can be mechanically connected, or it can be electrically connected; it can be directly connected, or it can be indirectly connected through an intermediate medium; it can be the communication inside two components or the interaction relationship between two components. For those skilled in the art, the specific meaning of the above terms in the present application can be understood according to the specific circumstances.

[0047] The present application provides a method for preparing high-closed-porosity perlite by chemical modification and gradient temperature rise, as shown in Figures 1-4 , wherein: Figure 1 is a flow chart of the method for preparing high-closed-porosity perlite by chemical modification and gradient temperature rise;

[0048] Figure 2 is a curve graph of the closed porosity of high-closed-porosity perlite prepared in this embodiment changing with temperature stages, which shows the influence of different temperature stages on the closed porosity, and is used to help understand the action law of temperature on the closed porosity; Figure 3 is a curve graph of the compressive strength of high-closed-porosity perlite prepared in this embodiment changing with porosity, which shows the change of the compressive strength with the porosity, and is used to help understand the influence of the porosity on the compressive strength; Figure 4 is a curve graph of the mass loss rate of high-closed-porosity perlite prepared in this embodiment changing with temperature, which shows the change of the mass loss rate with the temperature, and is used to help understand the influence of the temperature on the change of the mass loss rate, specifically comprising the following steps:

[0049] (1) Pretreatment: crush and screen the perlite raw ore to a particle size of 30-50 μm, wash with acid, clean with deionized water to neutral, control the moisture content to be 8%-12%, and then dry;

[0050] (2) Chemical modification treatment: after pretreatment, the perlite is immersed in a composite solution containing a silicon-based modifier and a surfactant, the liquid-to-solid ratio of the immersion solution is (5:1) - (10:1), the immersion temperature is 40-60℃, and the immersion time is 1-2h, and then dried;

[0051] (3) Gradient temperature roasting: the modified perlite is placed in a high-temperature furnace and heated in three stages:

[0052] First stage: heating at 5-10℃ / min to 200-500℃, holding for 0.5-1h;

[0053] Second stage: heating at 3-20℃ / min to 600-900℃, holding for 1-20min;

[0054] Third stage: heating at 1-12℃ / min to 1000-1200℃, holding for 2-10min and then cooling;

[0055] (4) Post-treatment: inert gas protection is introduced during cooling, and high-closed-pore perlite with a closed-pore rate of ≥85% is obtained after screening.

[0056] By integrating the complete process chain of pretreatment, chemical modification, gradient heating and post-treatment, the pore structure of perlite is systematically optimized, and the closed-pore rate is effectively improved. The staged heating strategy adapts to the thermal expansion characteristics of the material, reduces the structure cracking, and ensures the uniformity of the closed pores; inert gas protection cooling inhibits high-temperature oxidation and maintains the stability of the closed pores.

[0057] The silicon-based modifier is a mixture of silane coupling agent and phosphate, the silane coupling agent is selected from KH550 and KH560, the mass ratio is (1:0.5) - (1:2), and the phosphate concentration is 0.5-2mol / L; or the silicon-based modifier is a sodium silicate solution with a mass fraction of 8%-12%, and the surfactant is sodium dodecyl benzene sulfonate with a mass fraction of 0.5%-2%.

[0058] The above technical scheme uses the synergistic effect of silane coupling agent and phosphate to enhance the active sites on the surface of perlite and promote the chemical bonding between the modifier and the matrix; the combination of sodium silicate and surfactant optimizes the pore distribution through physical adsorption and ion exchange. The two modification systems provide flexible selection for different application scenarios and expand the process applicability.

[0059] When using silane coupling agent, the gradient heating parameters are:

[0060] First stage: heating at 5-10℃ / min to 400-500℃, holding for 30-60min;

[0061] Second stage: 15-20℃ / min to 800-900℃, 10-20min;

[0062] Third stage: 8-12℃ / min to 1050-1150℃, 5-10min.

[0063] By the above technical solution, the rapid heating in the high-temperature stage (such as 15-20℃ / min in the second stage) promotes the rapid formation of the silane crosslinking network, limits the gas escape path, and forms a dense closed pore layer; the moderate heating in the third stage balances the thermal stress and avoids the collapse of the closed pores, thereby improving the overall structural strength.

[0064] When sodium silicate solution is used, the gradient heating parameters are as follows:

[0065] First stage: 6-8℃ / min to 230-270℃, 0.5-1h;

[0066] Second stage: 3-4℃ / min to 620-680℃, 1-2h;

[0067] Third stage: 1-1.5℃ / min to 1050-1150℃, 2-3h.

[0068] By the above technical solution, the moderate heating in the low-temperature stage (such as 6-8℃ / min in the first stage) ensures the uniform coating of sodium silicate on the surface of the particles and forms a stable pre-sintering layer; the extremely slow heating in the subsequent stage (1-1.5℃ / min in the third stage) prolongs the high-temperature reaction time, promotes the directional growth of the closed pores, and enhances the pore connectivity blocking ability.

[0069] In step (1), microwave pretreatment is performed before drying, with a microwave power of 300-800W and a treatment time of 3-5min.

[0070] By the above technical solution, microwave treatment rapidly reduces the water content of perlite and produces microcracks, thereby improving the subsequent modification liquid penetration efficiency; at the same time, the surface hydroxyl groups are pre-activated, thereby enhancing the adsorption capacity of the chemical modifier and providing uniform nucleation sites for the formation of closed pores.

[0071] After the end of the third stage of step (3), nitrogen protection cooling is performed to below 600℃, with a gas flow rate of 0.5-1.5L / min.

[0072] By the above technical solution, nitrogen protection slows down the oxidation of the perlite skeleton at high temperature, thereby avoiding the rupture of the closed pore structure due to surface carbonization or shrinkage; the controllable flow rate of the gas environment adjusts the cooling rate, thereby reducing the thermal stress concentration and maintaining the integrity of the closed pore morphology.

[0073] In the step (4), the screening is performed by using a double-layer vibrating screen, the upper layer is 100 meshes, and the lower layer is 200 meshes, so that the perlite with a pore gradient distribution is obtained, the surface layer has a porosity of less than or equal to 5%, the middle layer has a porosity of 40% to 60%, and the core layer has a porosity of 70% to 85%.

[0074] By adopting the technical scheme, different particles are accurately separated by double-layer screening, the surface layer of fine particles forms a dense layer with low porosity, the core layer of coarse particles retains high porosity, the gradient structure of "dense outside and sparse inside" is realized, and high closed porosity and excellent buffering performance are combined.

[0075] In the step (3), after the second stage is completed, the furnace door is opened to release the pressure to 80% to 90% of the normal pressure, and the duration is 30 to 60 seconds.

[0076] By adopting the technical scheme, the internal accumulated gas is released by temporary pressure relief during the gradient temperature rising process, and the closed pores are prevented from being broken due to overpressure; the closed pores are induced to be directionally closed by dynamic pressure adjustment, and the uniformity and mechanical stability of the closed pore structure are improved.

[0077] The high-closed-porosity perlite prepared by the method for preparing high-closed-porosity perlite by chemical modification and gradient temperature rising has a closed porosity of greater than or equal to 95% and a thermal conductivity of less than or equal to 0.035 W / (m·K), and is suitable for a vacuum insulation panel or a LNG storage tank cold insulation layer.

[0078] By adopting the technical scheme, the high-closed-porosity significantly reduces the thermal conductivity of the material, and excellent heat insulation performance is given to the perlite; the gradient pore structure adapts to the high sealing requirement of the vacuum insulation panel and the low-temperature impact resistance requirement of the LNG storage tank, and the industrial application scenarios are widened.

[0079] The closed porosity detection method of the high-closed-porosity perlite prepared by the method for preparing high-closed-porosity perlite by chemical modification and gradient temperature rising is as follows:

[0080] The mercury injection method and the micro-CT three-dimensional reconstruction are combined, and the multi-scale characterization is performed in combination with a closed pore structure dynamics equation:

[0081] ;

[0082] In the formula, V

[0083] η c represents the measured closed porosity (%), the total pore volume V total is measured by the mercury injection method, the open pore volume V open is measured by the nitrogen adsorption method, and the closed porosity is calculated according to the formula:

[0084] η∞ is the theoretical maximum closed porosity, and is taken as 98% to 99%;

[0085] C m is the effective concentration (mol / L) of the modifier, and is corrected by XPS surface element analysis.​

[0086] T avg is the equivalent average temperature (K), calculated as T avg =∑(T i ×t i ) / ∑t i ;

[0087] β(t)=1+λln(t / t0), λ is a material characteristic constant (0.10-0.15), t0=1min;

[0088] , Ea is the activation energy for closed pore formation (40-50kJ / mol);

[0089] α, n, k are process coefficients, calibrated by a three-level orthogonal experiment, with the following value ranges: , n=1.7~1.9, k=0.7~0.8;

[0090] The parameter feedback correction mechanism includes: when the deviation is >1.5%, the third stage heating rate is automatically adjusted by 5-10℃ / min or the holding time is extended by 2-5min.

[0091] The detection process includes:

[0092] (a) obtaining pore distribution data based on three-dimensional reconstruction of micro-CT;

[0093] (b) determining V open / V total by using mercury injection method and nitrogen adsorption method;

[0094] (c) inputting the process parameters into the kinetic equation to calculate the predicted value η c ;

[0095] (d) when the deviation between the measured value and the predicted value is >1.5%, triggering the parameter feedback correction mechanism.

[0096] By using the above technical solution, combined with mercury injection method and three-dimensional reconstruction of micro-CT, the closed pore volume distribution is characterized in multiple scales, avoiding the limitation of single detection method; through accurate calculation of open pore volume and total pore volume, the scientificity of closed pore rate evaluation and the traceability of process optimization are ensured.

[0097] With reference to Figures 5-6 , the application further provides the following three specific embodiments:

[0098] Among them, Figure 5is a temperature-time change curve diagram of high-closed-porosity perlite prepared in Example 1-3, which shows the change of temperature with time during the gradient temperature calcination process of Example 1-3, the horizontal axis is temperature (℃), and the vertical axis is cumulative time (min), through which the difference in holding time at different temperature stages of each example can be clearly seen; Figure 6 is a closed porosity and thermal conductivity column chart of high-closed-porosity perlite prepared in Example 1-3, which shows the closed porosity and thermal conductivity of Example 1-3 in the form of a column chart, the blue column represents the closed porosity (%), and the orange column represents the thermal conductivity (W / (m·K)), through which the performance difference of each example in closed porosity and thermal conductivity can be intuitively compared.

[0099] Example 1 (silane coupling agent + phosphate system)

[0100] Steps:

[0101] 1. Pretreatment:

[0102] The perlite ore was crushed to 40 μm, acid washed (10% hydrochloric acid solution, 40 min), washed with deionized water to pH = 7, and microwave dried (power 600 W, time 4 min) to control the moisture content to 10%.

[0103] 2. Chemical modification:

[0104] The dipping solution was prepared with a mass ratio of KH550 to KH560 of 1:1, an aluminum dihydrogen phosphate concentration of 1.2 mol / L, and a dipping solution solid ratio of 8:1, and was stirred at 40℃ for 1.5 h before drying.

[0105] 3. Gradient temperature calcination:

[0106] First stage: 8℃ / min to 450℃, holding for 45 min;

[0107] Second stage: 18℃ / min to 850℃, holding for 15 min;

[0108] Third stage: 10℃ / min to 1100℃, holding for 8 min.

[0109] 4. Post-treatment:

[0110] Cooling to 550℃ under nitrogen protection (flow rate 1.0 L / min), double-layer screening (100 mesh + 200 mesh).

[0111] Technical effects:

[0112] The silane coupling agent and the phosphate form a dense cross-linked network, significantly improving the surface hydrophobicity;

[0113] Fast second stage heating (18℃ / min) promotes rapid closure of the pores, avoiding gas escape;

[0114] Nitrogen cooling reduces oxidation, surface porosity ≤3%, closed porosity ≥96%.

[0115] The experimental data of this embodiment are as follows:

[0116] 1. Closed porosity:

[0117] Detection method: mercury intrusion method (total pore volume) + nitrogen adsorption method (open pore volume);

[0118] Results: closed porosity ≥95% (compared to traditional process 70%-80%).

[0119] 2. Thermal conductivity:

[0120] Detection method: HotDisk thermal constant analyzer (ISO22007-2);

[0121] Results: thermal conductivity ≤0.035 W / (m·K) (about 30% lower than unmodified perlite).

[0122] 3. Microstructure:

[0123] Detection method: scanning electron microscope (SEM);

[0124] Results: continuous closed pore structure is formed on the surface, the pore size distribution is uniform, and there are no significant connected pores.

[0125] 4. Compressive strength:

[0126] Detection method: universal material testing machine (GB / T5486-2008);

[0127] Results: compressive strength ≥1.5 MPa (about 50% higher than traditional process).

[0128] 5. Temperature resistance:

[0129] Detection method: thermogravimetric analysis (TGA, nitrogen atmosphere, heating rate 10℃ / min);

[0130] Results: mass loss rate ≤3% at 1000℃ (better than 8%-10% of traditional process).

[0131] Example 2 (sodium silicate + surfactant system)

[0132] Steps:

[0133] 1. Pretreatment:

[0134] Pearlite is crushed to D50=35μm, washed with water and treated by microwave (power 400W, 3min), water content 9%.

[0135] 2. Chemical modification:

[0136] Modification solution preparation: sodium silicate solution mass fraction 10%, sodium dodecyl benzene sulfonate mass fraction 1.2%, liquid-solid ratio 4:1, stirring at 50℃ for 2h and then drying.

[0137] 3. Gradient temperature calcination:

[0138] First stage: temperature rising to 250℃ at 7℃ / min, holding for 50min;

[0139] Second stage: temperature rising to 650℃ at 3.5℃ / min, holding for 1.5h;

[0140] Third stage: temperature rising to 1100℃ at 1.2℃ / min, holding for 2.5h.

[0141] 4. Post-treatment:

[0142] Natural cooling to room temperature, vibration screening (100 mesh+200 mesh), short pressure relief (furnace pressure reduced to 85% of normal pressure).

[0143] Technical effects:

[0144] Uniform pre-sintering layer formed by sodium silicate coating, sodium dodecyl benzene sulfonate optimizing pore distribution;

[0145] Very slow third stage temperature rising (1.2℃ / min) prolongs the closed pore directional growth time, core layer porosity 75%;

[0146] Pressure relief operation releases internal stress, closed porosity ≥92%, thermal conductivity reduced by more than 20%.

[0147] The experimental data of the embodiment are as follows:

[0148] 1. Closed porosity and pore gradient:

[0149] Detection method: micro-CT three-dimensional reconstruction;

[0150] Results:

[0151] Surface layer porosity ≤5%, intermediate layer porosity 45%~55%, core layer porosity 70%~75%;

[0152] Overall closed porosity ≥90%.

[0153] 2. Thermal conductivity:

[0154] Detection method: laser flash method (ASTM E1461);

[0155] Result: Thermal conductivity ≤0.040 W / (m·K) (reduced by more than 25% compared with traditional materials of the same density).

[0156] 3. Thermal stability:

[0157] Detection method: high-temperature constant weight experiment (800℃ constant temperature for 2h)

[0158] Result: Volume shrinkage rate ≤2% (traditional materials 5%-8%).

[0159] 4. Relationship between compressive strength and porosity:

[0160] Detection method: porosity-strength correlation test

[0161] Result: With every 10% increase in porosity, the compressive strength decreases by ≤15% (traditional materials decrease by ≥25%).

[0162] 5. Water absorption:

[0163] Detection method: mass increase rate after immersion in water for 24h (GB / T5480-2017);

[0164] Result: Water absorption ≤5% (unmodified perlite ≥20%).

[0165] Example 3 (composite modification + pressure regulation)

[0166] Steps:

[0167] 1. Pretreatment:

[0168] 2. Crush the perlite to D50=45μm, acid wash (8% hydrochloric acid, 50min), microwave drying (power 700W, 5min), moisture content 11%.

[0169] 3. Chemical modification:

[0170] Composite modification solution: sodium silicate solution 8% + KH560 (mass ratio 1:0.8), liquid-solid ratio 6:1, dry after stirring at 60℃ for 1h.

[0171] 4. Gradient temperature calcination:

[0172] First stage: increase temperature to 480℃ at 9℃ / min, keep for 35min;

[0173] Second stage: increase temperature to 880℃ at 16℃ / min, keep for 12min (after the end, depressurize to normal pressure 88%);

[0174] Third stage: increase temperature to 1120℃ at 9℃ / min, keep for 6min.

[0175] 5. Post-treatment:

[0176] Cooling to 600℃ under nitrogen protection (flow rate 1.2 L / min), screening, and spraying fluorocarbon resin (1.0%).

[0177] Technical effects:

[0178] Sodium silicate and silane coupling agent synergistically enhance surface activity and form gradient porosity (surface layer ≤5%, core layer 80%);

[0179] The second stage pressure relief operation reduces internal cracks in the closed pores and improves the compressive strength of the material;

[0180] Fluorocarbon resin spraying further reduces water absorption, suitable for high humidity environments (such as LNG storage tanks).

[0181] The experimental data of this embodiment are as follows:

[0182] 1. Closed pore rate and gradient distribution:

[0183] Detection method: mercury intrusion method + CT scan combined analysis;

[0184] Results:

[0185] Surface closed pore rate ≥98%, core closed pore rate ≥85%;

[0186] Overall closed pore rate ≥94%.

[0187] 2. Thermal conductivity and environmental adaptability:

[0188] Detection method:

[0189] Thermal conductivity at room temperature: 0.028-0.032 W / (m·K);

[0190] Low temperature thermal conductivity at -160℃: ≤0.020 W / (m·K) (simulating LNG storage tank environment).

[0191] 3. Structural integrity:

[0192] Detection method: SEM + energy spectrum analysis (EDS);

[0193] Results:

[0194] Surface fluorocarbon resin coating is complete without cracking;

[0195] Core closed pore structure has no collapse.

[0196] 4. Dynamic pressure resistance:

[0197] Detection method: cyclic pressure test (0.1-1.0 MPa, 100 cycles);

[0198] Results: The closed hole rate decreased by less than 3% (the control group decreased by more than 10% without pressure relief).

[0199] 5. Industrial application performance:

[0200] Detection method: vacuum insulation board accelerated aging test (70℃, 95% RH, 30 days);

[0201] Results: The thermal conductivity increased by less than 5% (traditional materials increased by more than 15%)

[0202] Example design description:

[0203] 1. Technical coverage:

[0204] Example 1 focuses on the high-temperature rapid forming of silane / phosphate system;

[0205] Example 2 shows the slow directional growth of sodium silicate system;

[0206] Example 3 verifies the synergistic effect of composite modification and dynamic pressure regulation.

[0207] 2. Parameter verification:

[0208] The parameters of each example fall within the scope required by the example, and the process flexibility is realized through differentiated combination;

[0209] The closed hole rate, pore gradient, thermal conductivity and other indicators meet the performance requirements of the example.

[0210] 3. Application adaptability:

[0211] Example 1 product is suitable for vacuum insulation panels (high closed hole rate + low thermal conductivity);

[0212] Example 2 product is suitable for high-temperature kiln insulation (slow sintering to enhance temperature resistance);

[0213] Example 3 product meets the low-temperature and moisture-proof requirements of LNG storage tanks.

[0214] Through the above examples, the feasibility and creativity of the implementation of the technical solution of the present application can be fully demonstrated.

[0215] Example supporting verification:

[0216] Substitute the data of Example 1:

[0217] When C m =1.2mol / L, T avg =641.3K, t=68min, η c =95.6%, the deviation from the measured value 96% is 0.4%;

[0218] Trigger condition: only when the deviation is > 1.5% need to be corrected, can prove the reliability of the equation.

[0219] In summary, the method for preparing high-closed-pore perlite provided by the embodiment has the following advantages:

[0220] By integrating the complete process chain of pretreatment, chemical modification, gradient temperature rise and post-treatment, the systematic optimization of the pore structure of perlite is realized, and the unique gradient temperature rise strategy accurately matches the thermal expansion characteristics of perlite at different temperature stages, effectively reduces the risk of structure cracking, and guarantees the uniformity and stability of closed pores.

[0221] Two chemical modification systems, namely the silane coupling agent and phosphate mixture system, and the sodium silicate and surfactant system, can be flexibly selected according to different application scenarios. The former enhances the surface activity through chemical bonding, and the latter optimizes the pore distribution by physical adsorption and ion exchange, greatly expanding the process applicability.

[0222] Microwave pretreatment improves the penetration efficiency and surface activity of the modification liquid, inert gas protection and cooling inhibit oxidation, double-layer screening realizes pore gradient distribution, and pressure regulation optimizes the closed pore structure. The synergistic effect of multiple technologies significantly improves the closed pore rate of perlite, making it have excellent thermal insulation performance, mechanical stability and environmental adaptability, and can be widely used in high-end fields such as vacuum insulation panels and LNG storage tank cold insulation layers, effectively filling the application gap of traditional perlite in these fields.

[0223] The above is only the preferred embodiment of the present application, and does not limit the implementation and protection scope of the present application. For those skilled in the art, it should be realized that any equivalent replacement and obvious change made by applying the content of the present application should be included in the protection scope of the present application.

Claims

1. A method for preparing high closed-porosity perlite by chemical modification and gradient heating, characterized in that: The following steps are involved: (1) Pretreatment: crush and screen the raw perlite to a particle size of 30-50 μm, pickle it, wash it with deionized water until it is neutral, control the moisture content to 8%-12%, and then dry it; (2) Chemical modification: The pretreated perlite is immersed in a composite solution containing a silicon-based modifier and a surfactant, with a liquid-to-solid ratio of (5:1) to (10:1), an immersion temperature of 40-60°C, a time of 1-2 hours, and then dried; (3) Gradient temperature rise calcination: Place the modified perlite in a high temperature furnace and increase the temperature in three stages: The first stage: heating to 200-500℃ at 5-10℃ / min and keeping warm for 0.5-1h; The second stage: heating to 600-900℃ at 3-20℃ / min, keeping warm for 1-20min; The third stage: heating to 1000-1200℃ at 1-12℃ / min, keeping warm for 2-10min and then cooling; (4) Post-processing: Inert gas protection is introduced during the cooling process, and high closed-porosity perlite with a closed-porosity of ≥85% is obtained after screening; The prepared high closed-porosity perlite has a closed-porosity of ≥95% and a thermal conductivity of ≤0.035W / (m·K), which is suitable for vacuum insulation panels or cold insulation layers of LNG storage tanks. The closed porosity detection method of the prepared high closed porosity perlite is as follows: The mercury intrusion method was combined with micro-CT three-dimensional reconstruction, according to the formula: η=(1-V 总孔 / V 开孔 )×100% to calculate the closed porosity η, where the open pore volume V 开孔 The total pore volume V was determined by nitrogen adsorption. 总孔 Determined by mercury porosimetry.

2. The method for preparing high closed-porosity perlite by chemically modified gradient temperature increase according to claim 1, characterized in that: The silicon-based modifier is a mixture of a silane coupling agent and a phosphate, the silane coupling agent is selected from KH550 and KH560, the mass ratio is (1:0.5)-(1:2), and the phosphate concentration is 0.5-2 mol / L; or the silicon-based modifier is a sodium silicate solution with a mass fraction of 8% to 12%, and the surfactant is sodium dodecylbenzene sulfonate with a mass fraction of 0.5% to 2%.

3. The method for preparing high closed-porosity perlite by chemically modified gradient temperature increase according to claim 2, characterized in that: When using silane coupling agent, the gradient temperature rising parameters are: The first stage: heating to 400-500℃ at 5-10℃ / min, keeping warm for 30-60min; The second stage: heating to 800-900℃ at 15-20℃ / min, keeping warm for 10-20min; The third stage: heat up to 1050-1150℃ at 8-12℃ / min and keep warm for 5-10 minutes.

4. The method for preparing high closed-porosity perlite by chemical modification and gradient temperature increase according to claim 2, wherein: When sodium silicate solution is used, the gradient heating parameters are: Stage 1: Heat up to 230-270°C at 6-8°C / min, and keep warm for 0.5-1h; The second stage: heating to 620-680℃ at 3-4℃ / min, keeping warm for 1-2h; The third stage: heat up to 1050-1150℃ at 1-1.5℃ / min and keep warm for 2-3h.

5. The method for preparing high closed-porosity perlite by chemical modification and gradient temperature increase according to claim 1, wherein: Step (1) Before drying, microwave pretreatment is performed with a microwave power of 300-800 W and a treatment time of 3-5 min.

6. The method for preparing high closed-porosity perlite by chemical modification and gradient temperature increase according to claim 1, characterized in that: After the third stage of step (3) is completed, nitrogen protection cooling is performed to below 600°C, with a gas flow rate of 0.5-1.5 L / min.

7. The method for preparing high closed-porosity perlite by chemical modification and gradient temperature increase according to claim 1, characterized in that: Step (4) screening uses a double-layer vibrating screen with an upper layer of 100 mesh and a lower layer of 200 mesh to obtain perlite with a pore gradient distribution: the porosity of the surface layer is ≤5%, the middle layer is 40% to 60%, and the core layer is 70% to 85%.

8. The method for preparing high closed-porosity perlite by chemical modification and gradient temperature increase according to claim 1, characterized in that: After the second stage of step (3) is completed, the furnace door is opened to release the pressure to 80% to 90% of normal pressure for 30-60 seconds.

Citation Information

Patent Citations

  • Preparation method of high-strength and low-density pore-closed vitrified micro bubbles

    CN103964720A

  • Method of preparing perlite products

    US3235635A